ADVANCEMENTS IN GAS QUANTITY CONTROL DEVICES: INCREASING SENSITIVITY WITH GAINASSB STRUCTURE LIGHT DIODES - No'monov Sherzodbek; Matyoqubov Nozimjon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Introduction: The use of gas quantity control devices based on light-emitting diodes (LEDs) with GaInAsSb structures has been increasing in various industries due to their high sensitivity, selectivity, and fast response time. However, there is always a need to improve the sensitivity of these devices for better detection and measurement of gases. Therefore, this article aims to discuss the development of methods for increasing the sensitivity of gas quantity control devices based on GaInAsSb structure light diodes.